An Ontology-Based Utterance Interpretation in the Context of Intelligent Assistance - Paraiso, Emerson Cabrera; Barthès, Jean-Paul A. (Anais do Simpósio Brasileiro de Tecnologia da Informação e da Linguagem Humana (STIL); 2007: Anais do V Workshop em Tecnologia da Informação e da Linguagem Humana, 2007)
In this paper we present an ontology-based utterance interpretation in the context of intelligent assistance. Ontologies are used for syntactic and semantic interpretation and for task representation. This mechanism is embedded in a conversational interface applied to personal assistant agents. The main goal of this approach is to offer a system capable of performing tasks through an intuitive interface, allowing experienced and less experienced users to interact with it in an easy and comfortable way.